Evaluating the use of coronary artery calcium scoring as a tool for coronary artery disease (CAD) risk stratification and its association with coronary stenosis and CAD risk factors: a single-centre, retrospective, cross-sectional study at a tertiary centre in Pakistan - Afrose Liaquat; Ameerdad Khan; Saeed Ullah Shah; Hania Iqbal; Safa Iqbal; Atif Iqbal Rana; Habib Ur Rahman (BMJ Open)
Objective Coronary artery disease (CAD) risk stratification plays a fundamental role in the early detection and optimal management of CAD. The aim of our study is to investigate the use of coronary artery calcium scoring (CACS) as a tool for CAD risk stratification through evaluation of its correlation with the degree of coronary stenosis and its association with conventional cardiovascular risk factors in asymptomatic patients.Design Single-centre, retrospective, cross-sectional study.Setting The study was conducted at a tertiary centre (Shifa International Hospital) in Islamabad, Pakistan, through review of medical records of patients who underwent coronary CT between the years 2016 and 2020.Participants A total of 1014 patients were included in the study. The study population was analysed for presence of conventional risk factors (gender, age, diabetes, hypertension, body mass index, dyslipidaemia) and association with CACS (zero: n=534; minimal: 0 to ≤10, n=70; mild: >10 to ≤100, n=130; moderate: >100 to ≤400, n=118; and severe: >400, n=49). The association of CACS with the degree of coronary artery stenosis seen on CT scan (significant: ≥50% stenosis, n=216; non-significant: <50% stenosis, n=685) was also analysed.Outcome measures The main outcome was the association of coronary artery stenosis with CACS. The secondary outcome was the association of CACS with conventional CAD risk factors.Results A significant positive association was shown between CACS and coronary artery stenosis (zero vs minimal: OR 0.39, 95% CI 0.20 to 0.79, p=0.01; zero vs mild: OR 0.16, 95% CI 0.10 to 0.27, p<0.0001; zero vs moderate: OR 0.05, 95% CI 0.03 to 0.08, p<0.0001; zero vs severe: OR 0.02, 95% CI 0.01 to 0.050, p<0.0001). Age >45 (OR 1.03, 95% CI 1.01 to 1.05, p<0.0001), hypertension (OR 1.16, 95% CI 0.79 to 1.71, p=0.001) and diabetes (OR 1.33, 95% CI 0.88 to 1.99, p<0.0001) were associated with an increased risk of coronary artery stenosis. Moreover, plaques with higher calcium burden were found in the left anterior descending artery (mean CACS: 386.15±203.89), followed by right coronary (239.77±219.83) and left circumflex (175.56±153.54) arteries.Conclusion The results indicate a strong positive association of CACS with coronary artery stenosis. CACS was also significantly associated with conventional CAD risk factors in this population.